2014
DOI: 10.3912/ojin.vol19no02man05
|View full text |Cite
|
Sign up to set email alerts
|

Addressing Issues Impacting Advanced Nursing Practice Worldwide

Abstract: Advanced practice nursing roles are developing globally, and opportunities for advanced practice nursing are expanding worldwide due to the need for expert nursing care at an advanced level of practice. Yet it is well recognized that barriers exist with respect to APRNs being able to practice to the full extent of their education and training. Addressing barriers to APRN practice worldwide and ensuring that APRNs are able to practice to the full extent of their education and training can help to promote optima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 0 publications
0
19
0
7
Order By: Relevance
“…All the included sources were published between 1994 and 20 20, 39-73 and most (n = 24, 68.6%) were published from 2010 onward 39-60,66,69 . Nine articles included data about Saudi Arabia, 39,45,49-53,56,61 seven about Oman, 41,42,44,57,58,62,63 six about Jordan, 40,42,59,63,64,66 five about the United Arab Emirates, 42,43,46,61,63 three about Lebanon, 42,48,63 and three about Bahrain 42,55,63 . There were two articles each for Palestine, 54,67 Sudan, 63,68 Qatar, 42,47 and Tunisia 42,61 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All the included sources were published between 1994 and 20 20, 39-73 and most (n = 24, 68.6%) were published from 2010 onward 39-60,66,69 . Nine articles included data about Saudi Arabia, 39,45,49-53,56,61 seven about Oman, 41,42,44,57,58,62,63 six about Jordan, 40,42,59,63,64,66 five about the United Arab Emirates, 42,43,46,61,63 three about Lebanon, 42,48,63 and three about Bahrain 42,55,63 . There were two articles each for Palestine, 54,67 Sudan, 63,68 Qatar, 42,47 and Tunisia 42,61 .…”
Section: Resultsmentioning
confidence: 99%
“…Yemen 63 and Egypt 42 were each mentioned in one paper. Two sources included information from more than one Arab country, 42,63 and five included information on several countries, including Arab countries 53,57,58,61,62 . Gray literature from organizational websites incorporated data from Oman, 69,70 Lebanon, 60,71 Qatar, 72 Bahrain, 73 and Jordan 65…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many articles address the past and current educational, regulatory, and practice requirements for NPs internationally; 6,53,54 however, none address the transferability of NP credentials from one country to another. The review of the nursing regulatory bodies found in this article indicate that IENP transfers can and do occur.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) has acknowledged the need for APRNs in the Middle East, including Saudi Arabia [ 20 ]. However, various regulatory, institutional, and cultural barriers restrict the practice of APRNs.…”
Section: Barriers To Incorporating Aprns Into the Saudi Healthcare Systemmentioning
confidence: 99%